Development of a baseball-specific battery of tests and a testing protocol for college baseball players - Kohmura, Y.; Aoki, K.; Yoshigi, H.; Sakuraba, K.; Yanagiya, T. (The Journal of Strength and Conditioning Research, 2008)
In this study, the relationship between the physical fitness of college baseball players found from 6 field tests and a performance evaluation by coaches was investigated. The purpose was to ascertain whether the results would be similar to those obtained in a previous study. The subjects of the study were 43 college baseball players (mean age, 20.7 +/- 1.4 years; mean athletic career, 10.9 +/- 2.6 years). Referring to the previous study, the field tests of physical fitness were composed of 6 items: throwing distance, back strength, medicine ball throwing, standing long jump, T-test, and base running. For capabilities in batting, fielding, and running, the coach's evaluation was expressed by T scores. The results of the analysis indicated that those players with high evaluation scores had significantly better test results in comparison with those players who were rated low in the evaluation. Although the multiple regression models of the previous study were associated with a middle goodness of fit, a significant correlation was found between physical fitness found in the field tests and performance. The results from a partial correlation analysis indicated a significant correlation between the following: batting evaluation with back strength (p < 0.01) and medicine ball throwing (p <0.01); fielding evaluation with throwing distance (p < 0.05); and running evaluation with medicine ball throwing (p < 0.01), standing long jump (p < 0.05), T-test (p < 0.01), and base running (p < 0.01). It is certain that the performance of college baseball players is related to their physical fitness.